MODEL ANALISIS PENGUKURAN KINERJA PERUSAHAAN DENGAN MENGGUNAKAN INTEGRATED PERFORMANCES MEASUREMENT SYSTEM (IPMS) - Afferdhy Ariffien; Anggi Widia Purnama; Anisa Faizatun Yona Anggara3 (Organisasi Kreatif Indonesia Emas, 2024)
A manufacturing company producing crystal ice and block ice that prioritizes product quality and service quality. Located in the city of Bandung, the company's production is intended for the food and beverage industry to ice carving. In 2022 to 2023, there was a decline in sales from year to year at the XXX Ice Factory. This decline in sales indicates that the business is not growing, and the decline in productivity indicates that there are serious problems in it. In addition, as observed directly at PT XXX, there is an increase in increasingly competitive business competition in similar industries, especially in the current era. Therefore, every company must create and review the management of performance management that has been used in the sustainability of the company's business processes so that it can survive in the competitive market industry. In addition, PT XXX has never conducted a comprehensive performance measurement involving stakeholders. Factors that influence performance are based on several aspects that are indicators for measuring performance, namely human resources, work safety, finance, work facilities, Supplier Performance, and employee welfare. This company performance measurement assesses the company's performance in terms of financial and non-financial aspects. Company performance measurement using the Integrated Performance Measurement System (IPMS) method has 11 stakeholders in the company